2012
DOI: 10.1016/j.adolescence.2012.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Black hawk down?: Establishing helicopter parenting as a distinct construct from other forms of parental control during emerging adulthood

Abstract: The purpose of the current study was to establish a measure of helicopter parenting that was distinct from other forms of parental control, and to examine parental and behavioral correlates of helicopter parenting. Participants included 438 undergraduate students from four universities in the United States (M(age) = 19.65, SD = 2.00, range = 18-29; 320 women, 118 men), and at least one of their parents. Analyses revealed that helicopter parenting loaded on a separate factor from both behavioral and psychologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

29
454
4
22

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 403 publications
(509 citation statements)
references
References 61 publications
29
454
4
22
Order By: Relevance
“…Harper et al (2012) discovered that highly involved parents had children that were more socially satisfied with their college experience. Padilla-Walker and Nelson (2012) found that children of over-involved parents saw their relationship as "high in guidance, involvement, and emotional support" (p. 1186). Whether over-involvement causes more positive or negative outcomes is unclear.…”
Section: Over-involvementmentioning
confidence: 99%
See 4 more Smart Citations
“…Harper et al (2012) discovered that highly involved parents had children that were more socially satisfied with their college experience. Padilla-Walker and Nelson (2012) found that children of over-involved parents saw their relationship as "high in guidance, involvement, and emotional support" (p. 1186). Whether over-involvement causes more positive or negative outcomes is unclear.…”
Section: Over-involvementmentioning
confidence: 99%
“…Whether over-involvement causes more positive or negative outcomes is unclear. However, most researchers have suggested that parents who are overinvolved typically want the best for their child (Brussoni & Olsen, 2012;Givertz & Segrin, 2014;Padilla-Walker & Nelson, 2012;Segrin et al, 2012). Also, it has been discovered that the majority of parents are not over-involved, but it is important to understand the impact of those who are (Lowe et al, 2015).…”
Section: Over-involvementmentioning
confidence: 99%
See 3 more Smart Citations